Joomla! : 24-hour trainer - Kramer, Jen. (Indianapolis, IN : Wiley Pub., 2011)
Provides instructions for building a Joomla! website, covering such topics as purchasing a domain name, installing Joomla!, menu options, choosing and installing templates, adding extensions, creating and editing users, search engine optimization, and managing backups --
Book is accompanied by one DVD-ROM bearing the same call number and available at Makmal Digital, Perpustakaan Dr. Abdul Latiff.
System requirements for accompanying DVD-ROM: PC running Windows XP, Windows Vista, Windows 7, or later; or a Mac running OS X version 10.5.8 or later; a processor running at 1.6 GHz or faster; an internet connection; at least 1 GB of RAM; at least 3 GB of available hard disk space; a DVD-ROM drive.
Keywords: Joomla! (Computer file); Joomla! (Computer software); Web sites -- Authoring programs; Web site development; Web sites -- Design